2022
DOI: 10.4314/dujopas.v7i4a.1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular studies on extra-pulmonary tuberculosis among patients attending Aminu Kano Teaching Hospital, Kano, Kano State, Nigeria

Abstract: In 2010 World Health Organization reported that, one third of the World population had tuberculosis, and it is among the infectious disease with significant morbidity and mortality. Mycobacterium tuberculosis is a successful pathogen that has evolved several mechanisms to manipulate the host immune response. The purpose of this study was to determine the incidence of extra-pulmonary TB in patient that visited DOTs clinic, Aminu Kano Teaching Hospital, Kano Nigeria for treatment. A prospective cross-sectional l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…The findings of this study are in agreement with (WHO, 2019;Mohammad et al 2017;Mohammad et al, (2021) opined that this may not be unconnected with fact that patients in this age group are physically active and may be engaged in various sectors of life working experiences as such becoming more exposed to acquire and develop TB.In a related study Adesokan, (2014), identified contact with TB patient among other factors as significant potential in transmission of TB. In an earlier study Lawal et al (2009) revealed that, overcrowding, poor nutrition.…”
supporting
confidence: 89%
“…The findings of this study are in agreement with (WHO, 2019;Mohammad et al 2017;Mohammad et al, (2021) opined that this may not be unconnected with fact that patients in this age group are physically active and may be engaged in various sectors of life working experiences as such becoming more exposed to acquire and develop TB.In a related study Adesokan, (2014), identified contact with TB patient among other factors as significant potential in transmission of TB. In an earlier study Lawal et al (2009) revealed that, overcrowding, poor nutrition.…”
supporting
confidence: 89%